ChemInform Abstract: Solvent‐Free L‐Proline‐Catalyzed Domino Knoevenagel/6π‐Electrocyclization for the Synthesis of Highly Functionalized 2H‐Pyrans. Issue 8 (1st March 2013) - Pena, Javier; Moro, Rosalina F.; Basabe, P.; Marcos, Isidro S.; Diez, David
Abstract The pyrans are prepared from 3, 3‐dialkyl‐substituted α, β‐unsaturated aldehydes, including natural products, and β‐oxosulfones.